Maternal-Fetal Physiology, Intrapartum Care, Postpartum Care: A Team-Based Learning Module for Normal Obstetrics - Lindsey B. Sward; Sara G. Tariq (Association of American Medical Colleges, 2019)
Introduction Team-based learning (TBL) is an active learning strategy used at the University of Arkansas for Medical Sciences in both the preclinical and clinical years of medical school. The Department of Obstetrics and Gynecology (OB/GYN) uses TBLs during a 6-week clinical clerkship. This TBL is the first in a series of six and was designed to teach the topic of normal obstetrics to third-year medical students. Methods Prior to the TBL, students were provided with learning objectives and a list of advance preparation resources. These resources included a reading assignment from the student textbook, as well as optional online videos and optional online interactive quizzes. The students then came to class and completed an individual readiness assurance test (iRAT) and a group readiness assurance test (gRAT). The majority of in-class time was spent working through complex application exercises in the form of case vignettes. The TBLs were facilitated by a faculty member in the OB/GYN department. Results Since its initiation in June 2018, 93 students have participated in this TBL activity. The mean score on the iRAT was 88.9%, and the mean score on the gRAT was 98.8%. Ninety-eight percent of students reported that they were satisfied with this learning activity. Discussion This TBL was well received by students and unique in that it utilized a variety of types of advance preparation resources. With few other published OB/GYN TBLs available, we believe that this module could be a valuable resource for OB/GYN clerkships.